2010
DOI: 10.1097/jom.0b013e3181cc58ba
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Evaluation of Electronic Control Device Exposure in Law Enforcement Trainees: A Multisite Study

Abstract: The results from this large, multisite study suggest that, for most trainees, ECD exposure does not represent a significant health risk. Further investigation is warranted for cardiac vulnerability and potential interactions with ECD exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Similar to a study by Ho et al examining the effects of the TASER X26, we found clinically unimportant changes in sodium, potassium, or glucose immediately after the TASER X3 exposure [7]. Other authors have reported similar results [8,9].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar to a study by Ho et al examining the effects of the TASER X26, we found clinically unimportant changes in sodium, potassium, or glucose immediately after the TASER X3 exposure [7]. Other authors have reported similar results [8,9].…”
Section: Discussionsupporting
confidence: 89%
“…The CK at 24 h was 242.3 U/L, with a range of 52-909 [7]. Van Meenen et al had a mean baseline CK of 174.1 U/L and a 24-h mean CK of 181.4 [9]. In our study, the median baseline CK was 143 U/L, with a range of 12-651.…”
Section: Discussionmentioning
confidence: 50%
“…There was a change in pH from 7.45 to 7.42 at 1-minute after the 5-second discharge in this study, and lactate increased from 1.4 to 2.8 [9]. Other studies have shown no evidence of cardiac injury or arrhythmias based on troponin and surface electrocardiogram [10][11][12][13][14][15]. In a study by Ho et al a 15-second TASER X26 exposure led to a pH change from a baseline of 7.37-7.35 immediately after the exposure, having a trough of 7.33 at 2 min.…”
Section: Discussionmentioning
confidence: 43%
“…Ho et al 21 reported that all types of troponins measured were <0.2 ng/ml immediately, 8 h, and 24 h after TASER X26 "drive stun" applications in human volunteers. VanMeenen et al 57 also found no detectable levels of cardiac troponin I, in a group of 99 lawenforcement officers and trainees, 24 h after 5-s X26 ECD exposures.…”
Section: Ecdsmentioning
confidence: 91%